The Pendidikan Karakter Anak Usia Dini untuk Melatih Kendirian Melalui Bermain Bahan Alam - Siska Prifiantari (Jurnal Family Education, 2023)
The decline in the morals of the millennial generation, an era that is increasingly rampant with technological sophistication in the era of globalization has made a retreat in the moral quality of life of the Indonesian people today, especially among students and demands character education. This research uses the library research method. Data collection techniques are obtained from 11 kinds of journal articles related to the topic of discussion. It is very important to form the character of the child from an early age. A strong identity and character really need a systematic and well-organized coaching program. Child character education is not only carried out by the teacher, but the main task of parents is also to implement the child's character education at home. In carrying out character education, parents and teachers are role models to imitate and follow. Independence is the ability of the child to do everything independently, both related to his own activities and in everyday life, without being completely dependent on others. With the attitude of independence that the child has provides enormous benefits for himself including, 1) Children can move more freely to learn and interact with the surrounding environment; 2) Make them more confident and make things free; 3) Children are easy to play and interact well; 4) Easy to work and communicate with the child